Cryoconite pans on Snowball Earth: supraglacial oases for Cryogenian eukaryotes?. Issue 6 (15th July 2016) - Hoffman, P. F.
Abstract: Geochemical, paleomagnetic, and geochronological data increasingly support the Snowball Earth hypothesis for Cryogenian glaciations. Yet, the fossil record reveals no clear‐cut evolutionary bottleneck. Climate models and the modern cryobiosphere offer insights on this paradox. Recent modeling implies that Snowball continents never lacked ice‐free areas. Wind‐blown dust from these areas plus volcanic ash were trapped by snow on ice sheets and sea ice. At a Snowball onset, sea ice was too thin to flow and ablative ice was too cold for dust retention. After a few millenia, sea ice reached 100 s of meters in thickness and began to flow as a 'sea glacier' toward an equatorial ablation zone. At first, dust advected to the ablative surface was recycled by winds, but as the surface warmed with rising CO2, dust aka cryoconite began to accumulate. As a sea glacier has no terminus, cryoconite saturated the surface. It absorbed solar radiation, supported cyanobacterial growth, and sank to an equilibrium depth forming holes and decameter‐scale pans of meltwater. As meltwater production rose, drainages developed, connecting pans to moulins, where meltwater was flushed into the subglacial ocean. Flushing cleansed the surface, creating a stabilizing feedback. If the dust flux rose, cryoconite was removed; if the dust flux waned, cryoconite accumulated. In addition to cyanobacteria, modern cryoconite holes are inhabited by green algae, fungi, protists, and certain metazoans. On Snowball Earth, cryoconite pans provided stable interconnected habitats for eukaryotes tolerant of fresh to brackish cold water on an ablation surface 60 million km 2 in area. Flushing and burial of organic matter was a potential source of atmospheric oxygen. Dominance of green algae among Ediacaran eukaryotic primary producers is a possible legacy of Cryogenian cryoconite pans, but a schizohaline ocean—supraglacial freshwater and subglacial brine—may have exerted selective stress on early metazoans, or impeded their evolution.